2009
DOI: 10.1002/jbio.200910010
|View full text |Cite
|
Sign up to set email alerts
|

Chip scale integrated microresonator sensing systems

Abstract: Medicine, environmental monitoring, and security are application areas for miniaturized, portable sensing systems. The emerging integration of sensors with other components (electronic, photonic, fluidic) is moving sensing toward higher levels of portability through the realization of self-contained chip scale sensing systems. Planar optical sensors, and in particular, microresonator sensors, are attractive components for chip scale integrated sensing systems because they are small, have high sensitivity, can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
55
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 158 publications
(235 reference statements)
1
55
0
Order By: Relevance
“…Miniaturization of label-free optical sensors is of particular interest for realizing ultra compact lab-on-a-chip applications with dense arrays of functionalized spots for multiplexed sensing, that may lead to portable, low cost and low power devices [8]. Many efforts exist to realize small devices and among them are photonic crystal (PhC) fibers [9], microrings [6,10] and PhC cavities [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Miniaturization of label-free optical sensors is of particular interest for realizing ultra compact lab-on-a-chip applications with dense arrays of functionalized spots for multiplexed sensing, that may lead to portable, low cost and low power devices [8]. Many efforts exist to realize small devices and among them are photonic crystal (PhC) fibers [9], microrings [6,10] and PhC cavities [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Highly compact SOI sensor arrays are readily manufacturable using standard complementary metaloxide semiconductor processing. The use of ring resonators further amplifies the sensor response, because the light circulating in the ring effectively interacts with the same molecules many times [2,6,7]. These properties make Si wire resonators one of the most promising sensor platforms.…”
mentioning
confidence: 99%
“…Unfortunately, due to the large lattice mismatch, monolithic integration with silicon has proven to be difficult. Hybrid integration, whereby prefabricated components are integrated with the waveguides using accurate pick-and-place equipment does allow for prescreening of the lasers, but is not compatible with wafer scale integration, and hence, not suitable for use in combination with very dense optical network circuits [16]- [18]. Therefore, several research groups proposed and demonstrated an alternative integration process based on the use of wafer and/or die bonding [19]- [21].…”
Section: A Introductionmentioning
confidence: 99%